Association between the heart rate to temperature ratio and 28-day mortality in patients with heart failure in intensive care unit: a multicenter retrospective cohort study - Fu, Cheng; Lin, Weiguo; Chen, Xinglin; Hong, WeiLi; Yan, Shaorong; Lin, Yuzhan (Frontiers in Medicine, 2024)
BackgroundHeart failure (HF) is a life-threatening condition with a high mortality rate. The precise relationship between the heart rate and temperature (HR/T) ratio and mortality in patients with HF remains unclear. This study aimed to investigate the relationship between the HR/T ratio and 28-day intensive care unit (ICU) mortality rates in patients with HF.MethodsThis retrospective cohort study analyzed the data of 3,790 patients with congestive heart failure in a large electronic database. Patients were divided into quartiles based on their HR/T ratio: Q1 (1.28–1.76), Q2 (2.44–2.72), Q3 (2.88–3.14), and Q4 (3.29–4.13). Multivariable logistic regression analysis was performed to examine the association between HR/T ratio and 28-day ICU mortality.ResultsPatients with higher HR/T ratios had greater disease severity and higher mortality rates. In the fully adjusted regression model, a significant association was observed between HR/T ratio and 28-day ICU mortality risk, with mortality increasing as HR/T ratio rose (OR = 1.55, 95% CI: 1.17–2.04). An E-value analysis indicated that unmeasured confounders had a minimal impact on the results, confirming the robustness of the study.ConclusionAmong ICU-admitted patients with HF, we identified a significant association between HR/T ratio and 28-day ICU mortality. As the HR/T ratio increased, the 28-day ICU mortality showed an upward trend.